2015
DOI: 10.1167/iovs.15-16792
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Voluntary Exercise in an Inherited Retinal Degeneration Mouse Model

Abstract: Voluntary running partially protected against the retinal degeneration and vision loss that otherwise occurs in the rd10 mouse model of RP. This protection was prevented by injection of ANA-12, suggesting that TrkB activation mediates exercise's preservation of the retina. Exercise may serve as an effective, clinically translational intervention against retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 46 publications
1
53
0
1
Order By: Relevance
“…Voluntary exercise using running wheel for 6 weeks was also suggested to protect photoreceptor in the retinitis pigmentosa model in mice (Hanif et al. ). The underlying mechanisms of how exercise induces neuroprotection include upregulating neurotrophin expression, such as brain‐derived neurotrophic factor (BDNF), enhancing mitochondrial function and reducing inflammation.…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Voluntary exercise using running wheel for 6 weeks was also suggested to protect photoreceptor in the retinitis pigmentosa model in mice (Hanif et al. ). The underlying mechanisms of how exercise induces neuroprotection include upregulating neurotrophin expression, such as brain‐derived neurotrophic factor (BDNF), enhancing mitochondrial function and reducing inflammation.…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 99%
“…After 4 weeks of exercise (preconditioning of exercise for 2 weeks and additional 2 weeks of exercise after light exposure) at intensity of 10 metres/min, at a frequency of 5 days/ week, 60 min/day, was found to be effective in preserving function and count of photoreceptors in lightinduced retinal degenerative models in mice (Lawson et al 2014;Chrenek et al 2016). Voluntary exercise using running wheel for 6 weeks was also suggested to protect photoreceptor in the retinitis pigmentosa model in mice (Hanif et al 2015). The underlying mechanisms of how exercise induces neuroprotection include upregulating neurotrophin expression, such as brain-derived neurotrophic factor (BDNF), enhancing mitochondrial function and reducing inflammation.…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 99%
“…42, 46, 47, 50, 70–76 We found that retinal NR protection extends to these two arRP models (Fig 4-6), with significant increases of ERG amplitudes well after photoreceptor degeneration onset and retinal function loss in untreated cohorts. 42, 46, 47, 50, 7074, 76 The NR-induced increase in ERG mean amplitudes in IRBP KO mice, though significant (Fig. 4), was modest most likely because retinal function has not yet declined dramatically at this early stage in the degeneration.…”
Section: Discussionmentioning
confidence: 67%
“…rd10 mice on a C57BL/6J background 46, 47 were obtained from Jackson Laboratories (Bar Harbor, Maine). In the rd10 retina, rod cell death begins at about P15, and by P25 almost all of the rod photoreceptors have been lost.…”
Section: Methodsmentioning
confidence: 99%
“…Regular general physical exercise is not only a part of healthy life style, but also a rehabilitation strategy showing neuroprotective effects in numerous diseases. Recently, exercise has been proven to be neuroprotective in animal models of retinal degeneration [85][86][87]. Wild-type BALB/c mice were forced to exercise for 5 days/ week for 2 weeks before being exposed to bright light.…”
Section: Studies In Animal Modelsmentioning
confidence: 99%